Universally Composable Secure Two and Multi-party Computation in the Corruptible Tamper-Proof Hardware Token Model - Chandran, Nishanth; Chongchitmate, Wutichai; Ostrovsky, Rafail; Visconti, Ivan (CRYPTO 2019, 2019)
We introduce the corrupted token model. This model generalizes the tamper-proof token model proposed by Katz (EUROCRYPT '07) relaxing the trust assumption on the honest behavior of tokens. Our model is motivated by the real-world practice of outsourcing hardware production to possibly corrupted manufacturers. We capture the malicious behavior of token manufacturers by allowing the adversary to corrupt the tokens of honest players at the time of their creation. We show that under minimal complexity assumptions, i.e., the existence of one-way functions, it is possible to UC-securely realize (a variant of) the tamper-proof token functionality of Katz in the corrupted token model with n stateless tokens assuming that the adversary corrupts at most n-1 of them (for any positive n). We apply this result to existing multi-party protocols in Katz's model to achieve UC-secure MPC in the corrupted token model assuming only the existence of one-way functions. Finally, we show how to obtain the above results using tokens of small size that take only short inputs. The technique in this result can also be used to improve the assumption of UC-secure hardware obfuscation recently proposed by Nayak et al. (NDSS '17). While their construction requires the existence of collision-resistant hash functions, we can obtain the same result from only one-way functions. Moreover using our main result we can improve the trust assumption on the tokens as well.